2012
DOI: 10.2478/v10011-011-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α, HGF and TGF-β1 are Involved in Liver Regeneration Following Partial Hepatectomy Using Portal Vein Arterializations

Abstract: Kratak sadr`aj: Eksperimenti vezani za regeneraciju jetre posle parcijalne hepatektomije pokazali su da TNF-a, HGF i TGF-b1 kao i drugi citokini igraju va`ne uloge u razli~itim faza ma regeneracije jetre, me|utim, uticaj arterijalizacije port ne vene (APV) na ekspresiju ovih citokina tokom regene racije jetre nije jasan. Sprague Dawley pacovi nasumi~no su podeljeni u APV grupu i kontrolne grupe, a krv za detekciju ALT uzeta je pomo}u automatskog biohemijskog analiza tora. Ekspresije TNF-a, HGF i TGF-b1 u tkivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Previous work from our group suggested that the mechanisms behind LDABS-mediated liver regeneration differ from regeneration after PH alone. Specifically, fluorescent quantitative RT-PCR in our previous study revealed differential expression of TNF-α, HGF and TGF-β1 in the liver of rats with PH alone vs. with PH plus LDABS ( 21 ).…”
Section: Discussionmentioning
confidence: 93%
“…Previous work from our group suggested that the mechanisms behind LDABS-mediated liver regeneration differ from regeneration after PH alone. Specifically, fluorescent quantitative RT-PCR in our previous study revealed differential expression of TNF-α, HGF and TGF-β1 in the liver of rats with PH alone vs. with PH plus LDABS ( 21 ).…”
Section: Discussionmentioning
confidence: 93%
“…The animal models in groups A and B were prepared based on methods previously described ( 4 , 7 ). The animal model in group C was established on the basis of an improvement of the methods described by Schleimer et al ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…44 Higher rates of remnant liver regeneration and hepatocyte proliferation were reported in liver resection in PVA models than in models without ar terial supply (control group). [45][46][47][48][49] Moreover, cholestasis, bile duct injury, inflammation, energy state due to elevation in ATP content, hypoxia and hypoxia-associated gene changes were reported to be decreased with PVA compared to liver de-arterialization without reconstruction. 50,51 The hepatic artery provides the main oxygen supply to the biliary tract.…”
Section: Pathophysiologic Changes After Portal Vein Arterializationmentioning
confidence: 99%